Relations between the Church and the State in Lithuanian Constitutional Jurisprudence – separation or separateness? - Murauskas, Donatas (Teisė, 2018)
The article analyses current scholarship on the relations between the church and the state in the jurisprudence of Lithuanian Constitutional Court. Particular attention is drawn to the principle of the separateness of the state and the church (bažnyčios ir valstybės atskirumas) which is perceived as a peculiar feature of Lithuanian constitutional jurisprudence. The constitutional jurisprudence is analysed considering the concept of state-neutrality developed by representatives of political philosophy. The risks related to development of the constitutional idea of the cooperation of state and church in the light of state neutrality principle are identified.